Comparative Histopathological Effects of Several Non-Selective NSAIDs on Gastric Mucosa in Wistar Rats - Adenina, Syarinta; Amani, Patwa; Layal, Kamalia (Journal of Medicine and Health, 2025)
Non-selective NSAIDs are widely used for their anti-inflammatory effects. However, their use is limited by significant gastrointestinal side effects. Little is known about which NSAIDs cause more damage to the gastrointestinal. This study aims to compare the mucosal damage induced by various non-selective NSAIDs. Adult male Wistar rats were divided into six groups and administered different NSAIDs: mefenamic acid, diclofenac sodium, piroxicam, ibuprofen, aspirin, and a control group with distilled water. After five days of treatment, the rats were sacrificed, and their gastric tissues were examined both macroscopically and microscopically for signs of damage, including hemorrhagic injury, mucosal edema, epithelial cell loss, and inflammatory cell infiltration. All NSAID-treated groups exhibited significant gastric damage compared to the control group. Diclofenac sodium and piroxicam groups showed the most pronounced hemorrhagic injury, while piroxicam induced the most severe mucosal edema. Ibuprofen caused the highest level of inflammatory cell infiltration. Aspirin resulted in the least gastric histopathological damage score among the tested drugs. Among the tested NSAIDs, aspirin exhibited the least histopathological damage, suggesting a lower risk of gastric injury in this model